Ecological testing of Don rice varieties on the right bank of the Kuban River - P. I. Kostylev; E. V. Krasnova; A. V. Aksenov; M. A. Ladatko; I. A. Zeleneva; B. V. Foliyants (Зерновое хозяйство России)
The development of new rice varieties which form high productivity and are better adapted to the specific area where they will be further grown, plays a crucial role in rice productivity improvement. At the breeding institutes of the FSBSI “Federal Research Center of Rice” and the FSBSI “Agricultural Research Center “Donskoy”, the researchers have been studying for a long time and developing more productive and high-quality rice varieties that are resistant to adverse natural conditions. Individual genotypes of each variety determine different responses to the peculiarities of local environmental conditions that affect productivity level and the need for practice. The current paper is devoted to the analysis of the results of environmental trials of two Rostov and two Krasnodar rice varieties in the fields of 4 farms in the Krasnoarmeysky district of the Krasnodar Territory in 2023–2024, which revealed a significant difference in grain productivity. The conducted ecological trials of rice varieties ‘FNTsR’ and ‘ANTsD’ on the checks of four agricultural institutions of Krasnodar Krai showed significant variability of grain productivity depending on a forecrop. In the ES “Krasnaya”, on average for 2023–2024, the variety ‘Rapan 2’ was at the first place in productivity (7.95), the variety ‘Favorit’ was at the second place (7.50), the variety ‘Virasan’ was at the third place (6.47 t/ha). In the RPP “Krasnoarmeysky”, the varieties were ranked as follows: ‘Rapan 2’ (7.68), ‘Argamak’ (6.87 t/ha), ‘Favorit’ (6.72 t/ha). In the Agrocomplex “Cheburgolsky” they were ranked as follows: ‘Rapan 2’ (7.66 t/ha), ‘Favorit’ (7.40 t/ha), ‘Virasan’ (7.32 t/ha). In the Agrocomplex “Rossiya” they were ranked as follows: ‘Favorit’ (8.11 t/ha), ‘Argamak’ (7.34 t/ha), ‘Rapan 2’ (7.30 t/ha). For cultivation in rice farms of the Krasnodar Krai after soybean and sunflower there has been recommended the new highly productive rice variety ‘Argamak’, developed by the ARC “Donskoy”, is recommended.